INVESTIGATING THE DETERMINANTS OF MOOC CONTINUANCE INTENTION USING EXPECTATION-CONFIRMATION MODEL - LOH KAH HENG, ZAIM AZIZI ABU BAKAR, LOW KHAI ROL, LIM YOU PING, THERESA CHIEW (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Openness to MOOCs indicates the Initial stage of enrolling to a module conducted as MOOC. However, this does not guarantee the students will continue choosing other credit-bearing MOOCs in the University. This research examines the determinants of MOOC Continuance Intention among Taylor’s University students with regards to determinants such as apprehension, motivation, and openness to MOOCs, which is grounded on Expectancy-Confirmation Model- Information Technology (ECM-IT). There were 366 participants responding to the online survey carried out during the period of August 2021 to July 2022. The questionnaire included measurable constructs such as Computer Apprehension, Internet Apprehension, TIMES (Taylor’s Moodle) Apprehension and MOOC Apprehension as well as MOOC Motivation, MOOC Openness, MOOC-Acceptance Confirmation and MOOC Continuance Intention. Reliability test indicated high Cronbach’s alphas (internal consistency) for all constructs. Pearson correlation demonstrated that Computer Apprehension, Internet Apprehension, TIMES Apprehension impacted MOOC Apprehension which in turn influenced MOOC-Openness, MOOC-Motivation and MOOC- Continuance Intention.